Pengembangan Desain Antarmuka Sistem Evaluasi Proses Belajar Mengajar (PBM) Dengan Menggunakan Pendekatan Human Centered Design (HCD) (Studi Kasus : Jurusan Sistem Informasi FILKOM UB) - Raka Putra Pratama; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Information systems FILKOM UB is an educational institution that has an organizational structure and a lecturer-professor who teaches in the Department of information systems. When entering the final period of the semester, will conduct an evaluation of professors, how performance of the lecturer found on questionnaires in SIAM. However, the current shortfall to evaluate the performance results of the lecturers are still using paper print out so extravagant in the use of paper. Therefore required an evaluation system that was created to provide information and evaluation of lecturers that aims to simplify the evaluation of lecturers in order to be more effective and efficient. On this research will create a system of evaluation of the teaching and learning process (PBM) web-based. This research uses Human Centered Design as research methodology. To test your system using usability testing as his judgement, and also parameter using 3 metriks consisting of metrics, metrics of efficiency, effectiveness and satisfaction metrics. On the metrics obtained effectiveness trial results with 100% percentage of success. On efficiency metrics obtained the result total average time required in carrying out tasks in PBM evaluation system is less than 60 seconds. Get satisfaction metrics on the result of the dissemination of the questionnaire respondents amounted to 82.5 SUS where the results can be classified in 3 aspects of the assessment, the first